Exploring the Nutritional and Sensory Impact of Red Seaweed Fortification in Dark Chocolate: Red Seaweed Fortified Dark Chocolate - Debbarma, Jesmi; S., Sireesha; S., Remya; P., Viji; B., Madhusudana Rao (Fishery Technology, 2024)
The present study was aimed to develop seaweed-based chocolates and evaluate their nutritional, textural and sensory properties. Seaweed powder prepared from the red seaweeds Gracilaria edulis and Kappaphycus alvarezii was added separately to dark chocolate at different concentrations of 1%, 2.5%, 5%, and 7.5% (w/w) and stored under chilled condition (2-4˚°C) for further studies. Incorporation of seaweed in chocolate improved the protein and mineral content in the products. The addition of seaweed significantly (p